Effect of phytic acid from rice and corn on morphology, cell proliferation, apoptosis and cyclooxygenase-2 expression in swine jejunal explants - Elisângela Olegário da Silva; Juliana Rubira Gerez; Ana Paula Frederico Rodrigues Loureiro Bracarense (Ciência e Agrotecnologia, 2014)
Phytic acid (IP6) is a potent antioxidant present in several natural foods. Beneficial effects on colon cancer and inflammation have been associated to IP6 in several studies, however, scarce data about the effect on small intestine are available. The aim of the present study was to evaluate the effect of different doses of IP6 from rice and corn on intestinal morphology, cellular proliferation, apoptosis and cyclooxygenase-2 (Cox-2) expression using swine jejunal explants as experimental model. This report demonstrated that explants treated with 0.5 mM, 2.5 mM and 5 mM of IP6 from rice and 2.5 mM and 5 mM from corn showed higher villi height compared to control. Explants treated with 2.5 mM and 5 mM IP6 from rice exhibited a significant reduction on intestinal histological changes (villi atrophy and fusion, edema, lymphatic vessel dilation, loss of apical enterocytes, cell vacuolation, necrotic debris, morphology of enterocytes and microvilli and number of villi). The cellular proliferation decreased in the explants treated with the dosages of 2.5 mM and 5 mM from rice and a significant decrease in cell apoptosis was observed in the treatments with 2.5 mM IP6 from rice and 5 mM IP6 from corn compared to the control. The explants treated with 2.5 mM and 5 mM IP6 from rice and corn showed a significant reduction of the Cox-2 expression. Higher dosages of IP6 from rice and corn used in this experiment increased the viability and preservation of intestinal tissue as evidenced by morphological and immunohistochemical assays.